Treatment of cancer‐associated venous thromboembolism: 12‐month outcomes of the placebo versus rivaroxaban randomization of the SELECT‐D Trial (SELECT‐D: 12m). (26th February 2020) - Marshall, Andrea; Levine, Mark; Hill, Catherine; Hale, Danielle; Thirlwall, Jenny; Wilkie, Veronica; French, Karen; Kakkar, Ajay; Lokare, Anand; Maraveyas, Anthony; Chapman, Oliver; Arif, Azra; et al.
Abstract: Background: The Anticoagulation Therapy in Selected Cancer Patients at Risk of Recurrence of Venous Thromboembolism (SELECT‐D) trial demonstrated reduction in recurrent venous thromboembolism (VTE) but increased bleeding with rivaroxaban compared with dalteparin for treatment of acute VTE in cancer patients, at 6 months. Uncertainty remains around optimal duration of anticoagulation. Objectives: To assess VTE recurrence and bleeding, with anticoagulation or not, beyond 6 months. Patients/Methods: In SELECT‐D, after 6 months of trial treatment for VTE, patients with active cancer and residual deep vein thrombosis (RDVT) or index pulmonary embolism (PE) were eligible for randomization to a further 6 months of rivaroxaban or placebo. Patients with no RDVT stopped anticoagulation. Primary outcome was VTE recurrence at 12 months. The second randomization closed prematurely because of low recruitment when 92 of the planned 300 patients were recruited. Results: Ninety‐two of 136 eligible patients were randomized to rivaroxaban or placebo. The cumulative VTE recurrence after 6 months from the second randomization was 14% with placebo and 4% with rivaroxaban (hazard ratio, 0.32; 95% confidence interval [CI], 0.06‐1.58). The major and clinically relevant non‐major bleeding rates were 0% and 0% with placebo; and 5% (95% CI, 1‐18) and 4% (95% CI, 1‐17) with rivaroxaban. In an exploratory analysis, 7 (15%) of 46 placebo patients with RDVT or an index PE experienced recurrent VTE compared to none in the 35 patients in the RDVT‐negative cohort ( P  = .03). Conclusion: The SELECT‐D trial was underpowered to detect a statistically significant reduction in recurrent VTE with extended anticoagulation. The absence of RDVT and/or index PE, defined a population at low risk of recurrence.